Impact of Psychiatric and Related Somatic Medications on the Duration and Severity of COVID-19: A Retrospective Explorative Multi-center Study from the German Metropolitan Ruhr-area - Bonnet, Udo; Claus, BenediktBernd; Schaefer, Martin; Kuhn, Jens; Nyhuis, Peter; Scherbaum, Norbert; Brüne, Martin; Wakili, Velat; Juckel, Georg (Pharmacopsychiatry, 2021)
Introduction Several psychiatric and somatic medications are assumed to improve COVID-19-symptoms. These include antidepressants, antipsychotics, and anticonvulsants as well as anticoagulants, statins, and renin-angiotensin-aldosterone-system (RAAS)-inhibitors for somatic comorbid conditions. All these agents may reduce the hyperinflammatory response to SARS/CoV-2 or the related negative cardio-cerebrovascular outcomes.Methods In a retrospective longitudinal, multi-center inpatient study, we sought to explore the influence of psychiatric medications on COVID-19, comprising the period from diagnosing SARS/CoV-2-infection via PCR (nasopharyngeal swab) up to the next 21 days. Ninety-six psychiatric inpatients (mean age [SD] 65.5 (20.1), 54% females) were included. The primary outcome was the COVID-19-duration. Secondary outcomes included symptom severity and the presence of residual symptoms.Results COVID-19-related symptoms emerged in 60 (62.5%) patients, lasting 6.5 days on average. Six (6.3%) 56–95 years old patients died from or with COVID-19. COVID-19-duration and residual symptom-presence (n=22, 18%) were not significantly related to any substance. Respiratory and neuro-psychiatric symptom-load was significantly and negatively related to prescription of antidepressants and anticoagulants, respectively. Fatigue was negatively and positively related to RAAS-inhibitors and proton-pump-inhibitors, respectively. These significant relationships disappeared with p-value adjustment owed to multiple testing. The mean total psychiatric burden was not worsened across the study.Discussion None of the tested medications was significantly associated with the COVID-19-duration and -severity up to the end of post-diagnosing week 3. However, there were a few biologically plausible and promising relationships with antidepressants, anticoagulants, and RAAS-inhibitors before p-value adjustment. These should encourage larger and prospective studies to re-evaluate the influence of somatic and psychiatric routine medications on COVID-19-related health outcomes.
Keywords: antidepressants; antipsychotics; anticonvusants; anticoagulants; RAAS-inhibitors